LA CONCILIACIÓN EXTRAJUDICIAL ENTRE TRABAJADORES Y EMPLEADORES EN EL AMBITO LABORAL - Ugarte Vega Centeno, Máximo (2006)
The Out-of-Court conciliation is an alternative mechanism of conflicts resolution, by means of which, the parts involved satisfy their pretensions, nevertheless, in our society ther is a strong litigious culture and not conciliation. For this reason the author analyzes the advantages of the current Conciliation Law and its correspondent norms in the labor environment, emphasizing in achievements, like the reduction of costs and clearing the Judicial Power load process and the institutional establishment of the conciliation as a consensual mechanism that fortifies the social peace.